A new class of high-entropy fluorite oxides with tunable expansion coefficients, low thermal conductivity and exceptional sintering resistance. Issue 13 (October 2021) - Xu, Liang; Wang, Hongjie; Su, Lei; Lu, De; Peng, Kang; Gao, Hongfei
Abstract: High-temperature thermal barrier coating (TBC) materials are desired for the development of high-efficient gas turbines and diesel engines. Herein, to meet up with this requirement, a new class of high-entropy fluorite-type oxides (HEFOs) has been synthesized via a solid-state reaction method. Comparing to La2 Ce2 O7, a promising TBC material, the HEFOs exhibit similar high thermal expansion coefficients (TECs) of 11.92×10 −6 ∼12.11×10 −6 K -1 at temperatures above 673 K but a better TEC matching performance at the temperature range of 473–673 K. It is also found that through tuning the average A-site cation radius, the TEC of the HEFOs could be tailored efficiently. The HEFOs also possess low thermal conductivities of 1.52-1.55 W∙m -1 ∙K -1 at room temperature, which is much lower than that of La2 Ce2 O7 and comparable to pyrochlores as Gd2 Zr2 O7 . Moreover, the HEFOs display good sintering resistance and phase stability even at temperatures as high as 1873 K. The combination of these fascinating properties makes the HEFOs good candidates for thermal barrier coating and thermal insulating materials.